"The friendly Games"? The Melbourne Olympic Games in Australian culture 1946-1956 - Cahill, S. (1989)
Melbourne was making a concerted bid to obtain the centenary 1996 Olympic Games. While much of its bid is occupied with explanations of the city's ability to meet the International Olympic Committee's (IOC) requirements, it is underpinned by a common theme that the city possesses a unique quality of "Friendliness". This attribute originated in and characterised the 1956 Olympic Games